Wet cement mortar for three-dimensional modeling for construction and method for three-dimensional modeling for construction
The wet cement mortar formulation with specific dispersants and additives in a continuous mixing system addresses finish quality and curing speed issues, enabling rapid strength development and reduced dust in three-dimensional construction.
Patent Information
- Application Number
- JP2023542372
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-08-18
- Filing Date
- 2022-08-10
- Publication Date
- 2024-12-18
- Estimated Expiration
- 2042-08-10
AI Technical Summary
Existing cementitious materials for three-dimensional modeling in construction suffer from poor finish quality, dust generation, slow curing speed, and inadequate strength development, with no efficient methods for producing hardened cementitious bodies.
A wet cement mortar formulation containing specific ratios of lignin sulfonic acid and melamine sulfonic acid dispersants, diutan gum, setting retarders, amorphous calcium aluminosilicate, gypsum, and short fibers, mixed in a continuous mixing system, ensuring excellent self-supporting and strength development properties.
The formulation allows for constant material supply and lamination speed, enabling the construction of large-sized shaped bodies with rapid strength development and reduced dust, suitable for civil engineering applications.
Smart Images

Figure 0007602655000009 
Figure 0007602655000010 
Figure 0007602655000011
Abstract
Description
[Technical field]
[0001] The present invention relates to a wet cement mortar for three-dimensional modeling for construction, which is mainly used in the fields of civil engineering, architecture, and factory products, and a method for three-dimensional modeling for construction using the same. [Background technology]
[0002] In recent years, three-dimensional modeling technology has been used in the manufacturing industry to create models and parts. The technologies can be classified into three categories: photolithography (a method of curing and laminating UV-curable resin one layer at a time), inkjet method (a method of laminating by irradiating UV rays while spraying UV-curable resin from a printer head), powder gypsum modeling (a method of spraying resin or glue from a printer head and solidifying powder gypsum), powder sintering modeling (a method of laminating by baking resin or metal powder with a laser), and fused deposition modeling (a method of laminating by ejecting thermoplastic resin melted by heat from a thin nozzle). The objects are mainly made of resin, gypsum, and metal, and the technology of creating large objects such as construction materials using cementitious materials has been studied more overseas than in Japan. In Europe, the United States, and China, automatic construction machines are already being used to manufacture large objects at the level of detached houses.
[0003] For example, as a three-dimensional modeling technique using cementitious materials, Patent Document 1 discloses a technique in which three-dimensional data created by a computer is cut at a predetermined thickness to create two-dimensional slice data, and mortar mixed with an accelerator is sprayed onto a bed (table) while controlling the movement of a spray nozzle in the vertical and horizontal directions based on the two-dimensional slice data, and the sprayed mortar is allowed to harden independently to form a solidified layer of a shape based on the two-dimensional slice data, and the solidified layer formation work is repeated to sequentially stack in the vertical direction to form a shape. Patent Document 2 describes a material for making a mold for producing castings using a 3D printer, and discloses a material made of cement, sand, and a water-soluble silicate as an accelerator. Patent Documents 3 and 4 disclose a method for producing prefabricated members using a 3D printer and a method for producing a concrete earthquake-resistant wall using a 3D printer. Patent Document 5 discloses a technique related to a nozzle that ejects a material for 3D printing. Patent Document 6 discloses a method for producing a cementitious hardened body, characterized in that the cementitious hardened body is molded and produced using a resin formwork produced using a three-dimensional modeling system.
[0004] On the other hand, as a cementitious material, a material using a lignin sulfonate-based dispersant and a melamine sulfonate-based dispersant in combination is already known as a grout composition or a high-strength concrete composition (Patent Documents 7 and 8). Also, a PC grout material is known as a material using a dispersant and a thickener in combination (Patent Document 9). Furthermore, as a material containing calcium aluminate containing SiO2, a cement admixture characterized by having 300 parts by weight or less of gypsum and 0.1 to 20 parts by weight of a setting regulator per 100 parts by weight of calcium aluminosilicate glass, and a cement composition in which the cement admixture is mixed with the cement (Patent Document 10), as well as a cement composition containing calcium aluminosilicate with a CaO / Al2O3 molar ratio of 2.0 to 3.5 and a SiO2 content of 10 to 25%, and one or more selected from latent hydraulic substances and pozzolanic substances (Patent Document 11), etc. are known.
[0005] Furthermore, a cementitious material for three-dimensional modeling for construction is known that contains cement, aggregate, a dispersant in which the mass ratio of a lignin sulfonate-based dispersant to a melamine sulfonate-based dispersant is R:M=100:80-400, a thickener, a setting retarder, amorphous calcium aluminosilicate containing 10-25% SiO2 in oxide equivalent, gypsum, and short fibers (Patent Document 12).
[0006] Furthermore, a continuous mixing and spraying construction system and a spraying construction method (Patent Document 13) are known that can continuously mix and spray dry cement mortar containing a highly viscous polymer with stable quality. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 10-235623 [Patent Document 2] U.S. Patent No. 8,211,226 [Patent Document 3] China Patent Publication No. 104308988 [Patent Document 4] China Patent Publication No. 104153493 [Patent Document 5] US Patent Application Publication No. 2014 / 0308381 [Patent Document 6] JP 2016-101737 A [Patent Document 7] JP 2008-247677 A [Patent Document 8] Special Publication No. 62-10949 [Patent Document 9] JP 2006-290694 A [Patent Document 10] Japanese Patent Application Publication No. 4-97932 [Patent Document 11] JP 2006-232603 A [Patent Document 12] JP 2018-140906 A [Patent Document 13] JP 2007-245596 A Summary of the Invention [Problem to be solved by the invention]
[0008] Patent Document 1 is a technology in which dry mix mortar, which is a premix of cement and fine aggregate, and water containing an accelerator are sprayed while being mixed and stirred with a spray nozzle to harden the mortar by itself, which leads to problems such as poor finish of the molded object and dust generation. Patent Document 2 uses a water-soluble silicate as an accelerator, which leads to problems such as slow hardening speed and poor strength development. Patent Documents 3 and 4 relate to a technology for manufacturing components with a 3D printer, and there is no mention of the use of a specific material. Patent Document 5 relates to the shape of the nozzle of a 3D printer, and there is no mention of the use of a specific material. Patent Document 6 relates to a technology for manufacturing a cementitious hardened body by molding a resin mold with a 3D printer and filling the mold with a cementitious material, and there is a problem that the molded cementitious hardened body cannot be efficiently manufactured because the mold must be made. Although various cementitious materials are known, as described in Patent Documents 7 to 11, no cementitious material capable of solving the above problems is known. Furthermore, Patent Document 12 is a cementitious material for three-dimensional modeling for construction, but there is no description of a mixing method, and no description of obtaining a sufficient construction speed. Patent Document 13 is a spraying construction system, which is different from the use for three-dimensional modeling for construction.
[0009] In view of the above problems, the present invention aims to provide a wet cement mortar for three-dimensional modeling for construction, which has excellent self-supporting properties and short-term and long-term strength development properties, and a method for three-dimensional modeling for construction using the same. [Means for solving the problem]
[0010] As a result of various investigations conducted in order to solve the above-mentioned problems, the present inventors have found that the above-mentioned problems can be solved by using a wet cement mortar prepared by mixing, in a continuous mixing system, a dry cementitious material containing aggregate, a dispersant containing a lignin sulfonate-based dispersant and a melamine sulfonate-based dispersant in a specific ratio, diutan gum having an average molecular weight in the range of 2 million to 8 million and a viscosity of a 0.25% aqueous solution in the range of 2,000 to 10,000 mPa s, a set retarder, amorphous calcium aluminosilicate containing SiO2 in a specific ratio, gypsum, and short fibers, and have completed the present invention. The present invention relates to the following. (1) A wet cement mortar for three-dimensional modeling for construction, which is continuously mixed in a continuous mixing system having a device (A) for continuously supplying a dry cementitious material for three-dimensional modeling for construction, a device (B) for continuously supplying water, and a cylindrical agitator (C) having a horizontal screw shaft that can continuously mix them to produce wet mortar, the device (A) continuously supplying water, and a cylindrical agitator (C) having a horizontal screw shaft that can continuously mix them to produce wet mortar. The continuous mixing system has a device (A) for continuously supplying water, a device (B) for continuously supplying water, and a cylindrical agitator (C) having a horizontal screw shaft that can continuously mix them to produce wet mortar, the device (A) ... (2) The wet cement mortar for three-dimensional modeling for construction according to the above (1), containing 13 to 20 parts by mass of water per 100 parts by mass of the dry cementitious material for three-dimensional modeling for construction. (3) The wet cement mortar for three-dimensional fabrication for construction according to the above (1) or (2), wherein the amount of the dispersant (C) used is 0.2 to 3 parts by mass per 100 parts by mass of the cement (A). (4) The wet cement mortar for three-dimensional fabrication for construction according to any one of the above (1) to (3), wherein the amount of the diutan gum (D) used is 0.03 to 1.0 part by mass per 100 parts by mass of the cement (A). (5) The wet cement mortar for three-dimensional modeling for construction according to any one of (1) to (4) above, wherein the amount of the gypsum (G) used is 50 to 250 parts by mass per 100 parts by mass of the amorphous calcium aluminosilicate (F). (6) The wet cement mortar for three-dimensional modeling for construction according to any one of (1) to (5) above, wherein the total amount of the amorphous calcium aluminosilicate (F) and the gypsum (G) used is 5 to 30 parts by mass per 100 parts by mass of the cement (A). (7) The wet cement mortar for three-dimensional fabrication for construction according to any one of the above (1) to (6), wherein the aggregate (B) includes a balloon-type aggregate. (8) The wet cement mortar for three-dimensional modeling for construction according to any one of the above (1) to (7), wherein the set retarder (E) contains an oxycarboxylic acid. (9) The wet cement mortar for three-dimensional fabrication for construction according to any one of the above (1) to (8), wherein the short fibers (H) have an average fiber length of 5 to 15 mm. (10) The wet cement mortar for three-dimensional modeling for construction according to the above (9), wherein the short fibers (H) have an average fiber diameter of 20 to 250 μm and the number of fibers per gram is 5,000 or more. (11) A method for three-dimensional modeling for construction, comprising pumping the wet cement mortar for three-dimensional modeling for construction described in any one of (1) to (10) above, and stacking the wet mortar for three-dimensional modeling for construction discharged from a nozzle while moving the nozzle, thereby constructing a modeled object. (12) The method for three-dimensional modeling for construction according to the above (11), wherein the pump is a rotary positive displacement uniaxial eccentric screw pump. Effect of the Invention
[0011] By using the wet cement mortar for three-dimensional modeling for construction and the three-dimensional modeling method for construction of the present invention, it is possible to supply a constant amount of material and ensure a constant layering speed. In addition, since excellent self-supporting property and strength development are obtained, a large model can be constructed in a short time. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a schematic diagram showing an example of a continuous mixing system used for producing the wet cement mortar for three-dimensional modeling for construction of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing an example of a three-dimensional modeling system used in the three-dimensional modeling method for construction of the present invention. [Diagram 3] FIG. 3(a) is a schematic diagram of the spray nozzle as viewed from the side, and FIG. 3(b) is a schematic diagram of the spray nozzle as viewed from the discharge port side. [Figure 4] FIG. 4 is a schematic diagram of a three-dimensional object produced in Example 8 described later. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] In the present invention, "3D modeling" refers to a technology for manufacturing molded bodies of any shape by directly layering a cross-sectional shape based on 3D data without using dedicated tools such as molds. "3D modeling" is also called "layered modeling" or "rapid prototyping."
[0014] (Wet cement mortar for construction 3D modeling) The wet cement mortar for three-dimensional modeling for construction of the present invention is continuously mixed in a continuous mixing system having a device (A) for continuously supplying a dry cementitious material for three-dimensional modeling for construction containing cement (A), aggregate (B), a dispersant (C) in which the mass ratio of a lignin sulfonic acid dispersant (R) to a melamine sulfonic acid dispersant (M) is R:M=100:80-400, diutan gum (D) having an average molecular weight in the range of 2 million to 8 million and a viscosity of a 0.25 mass% aqueous solution in the range of 2000 to 10000 mPa·s, a retarder (E), amorphous calcium aluminosilicate (F) containing 10 to 25 mass% SiO2 in terms of oxide, gypsum (G), and short fibers (H), a device (A) for continuously supplying water (B), and a cylindrical agitator (C) containing a horizontal screw shaft that can continuously mix them to produce wet mortar. As a result, the wet cement mortar for three-dimensional modeling for construction of the present invention has excellent self-supporting properties, as well as short-term strength development and long-term strength development properties.
[0015] [Dry cementitious material for 3D modeling] The dry cementitious material for 3D printing used in the wet cement mortar for 3D printing for construction of the present invention (hereinafter, may be simply referred to as "dry cementitious material") includes cement (A), aggregate (B), dispersant (C) in which the mass ratio of a lignin sulfonate-based dispersant (R) to a melamine sulfonate-based dispersant (M) is R:M=100:80-400, diutan gum (D) having an average molecular weight in the range of 2 million to 8 million and a viscosity of a 0.25 mass% aqueous solution in the range of 2000 to 10000 mPa s, a setting retarder (E), amorphous calcium aluminosilicate (F) containing 10 to 25 mass% SiO2 calculated as oxide, gypsum (G), and short fibers (H).
[0016] <Cement (A)> The cement (A) used in the present invention may be any of various Portland cements, such as ordinary, early strength, super early strength, low heat, and moderate heat, or any of various blended cements obtained by mixing these Portland cements with blast furnace slag, fly ash, or silica, or any of various blended cements having a Blaine specific surface area of 2000 cm 2Examples of suitable cement include filler cements containing limestone powder or blast furnace slag powder with a specific surface area of 2000 cm2 or more, environmentally friendly cements (eco-cement) made from municipal waste incineration ash or sewage sludge incineration ash, and alumina cements used for refractory materials. One or more of these can be used. The Blaine specific surface area of cement (A) is 2000 cm2. 2 / g or more is preferable, and 3000 cm 2 The upper limit of the range of the Blaine specific surface area of the cement (A) is not particularly limited, but is usually 5000 cm 2 / g.
[0017] <Aggregate (B)> The aggregate (B) used in the present invention is not particularly limited, and commercially available aggregates derived from natural limestone, aggregates derived from siliceous materials, and heavy aggregates with a specific gravity exceeding 3.0 can be used. In addition, in order to improve self-supporting property, a part of the aggregate used may be a balloon-type aggregate. The balloon-type aggregate is generally called a lightweight aggregate, and examples thereof include fly ash balloons, shirasu balloons, and balloons obtained by firing and foaming obsidian in a kiln. The specific gravity of the aggregate (B) is preferably 3 or less, more preferably 2.0 or less, more preferably 1.8 or less, and most preferably 1.0 or less. In addition, the lower limit of the range of the specific gravity of the aggregate (B) is not particularly limited, but is usually 0.3. The maximum particle size of the aggregate (B) (including balloon-type aggregate) is preferably 10 mm or less, more preferably 5 mm or less, in consideration of pumpability. The lower limit of the maximum particle size range of the aggregate (B) is not particularly limited, but is usually 0.03 mm. The amount of aggregate (B) used is preferably 50 to 300 parts by mass, more preferably 100 to 200 parts by mass, per 100 parts by mass of cement (A). When the amount of aggregate (B) used is 50 parts by mass or more per 100 parts by mass of cement (A), self-supporting property is easily ensured. When the amount of aggregate (B) used is 300 parts by mass or less per 100 parts by mass of cement (A), appropriate softness is easily ensured, and pumpability is improved. When using a balloon-type aggregate, the amount used is preferably 25 parts by mass or less, more preferably 1 to 25 parts by mass, and even more preferably 3 to 15 parts by mass, per 100 parts by mass of aggregate (B). When the amount of balloon-type aggregate used is 25 parts by mass or less per 100 parts by mass of aggregate (B), strength expression is high and appropriate softness is secured, resulting in good pumpability. On the other hand, when the amount of balloon-type aggregate used is 1 part by mass or more per 100 parts by mass of aggregate (B), an even higher improvement in self-supporting property is obtained.
[0018] <Dispersant (C)> The dispersant (C) used in the present invention is a dispersant consisting of a lignin sulfonate-based dispersant (R) and a melamine sulfonate-based dispersant (M), and is a dispersant in which the lignin sulfonate-based dispersant (R) and the melamine sulfonate-based dispersant (M) are used in combination at a mass ratio of R:M=100:80-400. By using such a dispersant (C), the fluidity of the cementitious material kneaded with water can be ensured and the thixotropic property (thixotropy) can be improved. The ratio is more preferably R:M=100:100-250. If the blending ratio of the melamine sulfonate-based dispersant (M) is less than the lower limit, the amount of dispersant required to obtain the desired fluidity will increase, and the fluidity will change too much over time, which may hinder pumping. If the blending ratio of the melamine sulfonate-based dispersant (M) is more than the upper limit, setting will be delayed and the fluidity will change little over time, making it difficult to ensure self-supporting properties after pumping. The amount of dispersant (C) used is preferably 0.2 to 3 parts by mass, more preferably 0.5 to 2 parts by mass, per 100 parts by mass of cement (A). When the amount of dispersant (C) used is 0.2 parts by mass or more per 100 parts by mass of cement (A), sufficient fluidity can be easily obtained. When the amount of dispersant (C) used is 3 parts by mass or less per 100 parts by mass of cement (A), setting is delayed and the change in fluidity over time can be further suppressed from becoming small, and as a result, self-supporting property can be further improved.
[0019] <Diutan gum (D)> In the present invention, diutan gum (D) having an average molecular weight in the range of 2 million to 8 million and a viscosity of a 0.25% by mass aqueous solution in the range of 2000 to 10000 mPa·s can be used. Here, the viscosity of a 0.25% by mass aqueous solution is a value measured at 25°C using a B-type viscometer at 3 rpm. Diutan gum is, for example, a natural polymer polysaccharide having two glucose units, one glucuronic acid unit, and three rhamnose units as constituent units. By using such diutan gum (D), thixotropy can be imparted to the wet cement mortar for three-dimensional modeling for construction of the present invention. From this viewpoint, the average molecular weight of diutan gum (D) is preferably 2.5 million to 6 million, and the viscosity of a 0.25% by mass aqueous solution is preferably 2500 to 8000 mPa·s. The amount of diutan gum (D) used is preferably 0.03 to 1.0 part by mass, more preferably 0.05 to 0.5 part by mass, per 100 parts by mass of cement (A). When the amount of diutan gum (D) used is 0.03 part by mass or more per 100 parts by mass of cement (A), more sufficient thixotropy can be imparted. When the amount of diutan gum (D) used is 1.0 part by mass or less per 100 parts by mass of cement (A), pumpability and strength development become more excellent.
[0020] <Set retarder (E)> The retarder (E) used in the present invention may be any of those commercially available for cementitious materials. Examples of the retarder (E) include inorganic retarders such as phosphates, silicofluorides, copper hydroxide, boric acid or its salts, zinc oxide, zinc chloride, and zinc carbonate, and one or more of these may be used in combination. Examples of the retarder (E) include organic retarders such as oxycarboxylic acids (citric acid, gluconic acid, malic acid, tartaric acid, glucoheptonic acid, oxymalonic acid, lactic acid, etc.) or their salts (hereinafter, oxycarboxylic acids and salts of oxycarboxylic acids may be collectively referred to as oxycarboxylic acids), and sugars, and one or more of these may be used in combination. Furthermore, the retarder (E) may be a mixture of inorganic compounds such as carbonates, bicarbonates, nitrates, hydroxides, and silicates, and the above-mentioned oxycarboxylic acids or their salts. Among these, those containing an oxycarboxylic acid are preferred, from the viewpoint of improving pumpability and easily ensuring self-supporting properties after pumping, and oxycarboxylic acids alone or a mixture of an oxycarboxylic acid and an inorganic compound are more preferred. The amount of the set retarder (E) used is preferably 0.05 to 0.7 parts by mass, more preferably 0.07 to 0.5 parts by mass, per 100 parts by mass of cement. When the amount of the set retarder (E) used is 0.05 parts by mass or more per 100 parts by mass of cement, it becomes easy to ensure the pot life considering the mixing time and pumping. When the amount of the set retarder (E) used is 0.7 parts by mass or less per 100 parts by mass of cement, it is possible to prevent the setting time from becoming too long and the inability to ensure self-supporting properties.
[0021] <Amorphous calcium aluminosilicate (F)> The amorphous calcium aluminosilicate (F) used in the present invention (hereinafter simply referred to as "calcium aluminosilicate") is obtained by subjecting a mixture of CaO raw material, Al2O3 raw material, and SiO2 raw material to heat treatment such as firing in a kiln or melting in an electric furnace, and is an amorphous calcium aluminosilicate containing 10 to 25 mass% of SiO2 in oxide equivalent. Since calcium aluminosilicate is amorphous, it has high reactivity. If the SiO2 content is less than 10 mass%, the hydration activity becomes high, and the amount of setting retarder required to adjust the hardening time increases, which may affect thixotropy and self-supporting property, and if it exceeds 25 mass%, the hydration activity becomes low, and there is a possibility that an appropriate hardening speed cannot be obtained. From this viewpoint, the SiO2 content in oxide equivalent in the amorphous calcium aluminosilicate (F) is preferably 12 to 20 mass%. The calcium aluminosilicate (F) preferably has a molar ratio of CaO to Al2O3 calculated as oxide, CaO / Al2O3, of 1.5 to 3.5, more preferably 1.7 to 2.0. In addition, the calcium aluminosilicate (F) may contain, as other components, partial solid solution of alkali metals such as sodium, potassium, and lithium. The particle size of calcium aluminosilicate (F) is 3000 cm in Blaine value. 2 / g or more. The particle size of calcium aluminosilicate (F) is 3000 cm 2 / g or more, the strength development is further improved. From this viewpoint, the particle size of the calcium aluminosilicate (F) is more preferably 4000 cm in Blaine value or more. 2 / g or more. The upper limit of the particle size range of calcium aluminosilicate (F) is not particularly limited, but is usually 7000 cm in Blaine value. 2 / g.
[0022] <Gypsum (G)> The gypsum (G) used in the present invention is a component that further improves strength when used in combination with the calcium aluminosilicate. Types of gypsum (G) include anhydrous gypsum, hemihydrate gypsum, dihydrate gypsum, etc., and gypsum produced as a by-product in factories or naturally occurring gypsum can be used. Among these, the use of anhydrous gypsum is preferred in terms of strength development. The grain size of gypsum (G) is 3000 cm in Blaine value. 2 / g or more. The particle size of gypsum (G) is 3000 cm 2 / g or more, the strength development is further improved. From this viewpoint, the particle size of gypsum (G) is set to 4000 cm in Blaine value. 2 The upper limit of the particle size range of gypsum (G) is not particularly limited, but is usually 7000 cm 2 / g. The amount of gypsum (G) used is preferably 50 to 250 parts by mass, more preferably 100 to 200 parts by mass, per 100 parts by mass of calcium aluminosilicate (F). When the amount of gypsum (G) used is 50 parts by mass or more per 100 parts by mass of calcium aluminosilicate (F), the strength can be further improved. When the amount of gypsum (G) used is 250 parts by mass or less per 100 parts by mass of calcium aluminosilicate (F), the strength development can be increased according to the amount of gypsum (G) used.
[0023] The total amount of calcium aluminosilicate (F) and gypsum (G) used is preferably 5 to 30 parts by mass, more preferably 10 to 20 parts by mass, per 100 parts by mass of cement (A). When the total amount of calcium aluminosilicate (F) and gypsum (G) used is 5 parts by mass or more per 100 parts by mass of cement (A), the strength enhancing effect of calcium aluminosilicate (F) and gypsum (G) is further enhanced. When the total amount of calcium aluminosilicate (F) and gypsum (G) used is 30 parts by mass or less per 100 parts by mass of cement (A), the pot life is further ensured, and the strength development is further improved.
[0024] <Short Fiber (H)> The short fibers (H) used in the present invention may be any commercially available short fibers for cement mixing. Examples of the short fibers (H) include vinylon fibers, acrylic fibers, nylon fibers, steel fibers, glass fibers, polypropylene fibers, polyethylene fibers, polyester fibers, and basalt fibers, and it is also possible to use one or more of these fibers in combination. Among these, it is preferable to use vinylon fibers, which have a wide variety of fiber diameters and lengths, and nylon fibers, which have excellent dispersibility. Considering that the short fibers (H) are premixed in advance, the average fiber length is preferably in the range of 3 to 15 mm, more preferably in the range of 5 to 10 mm. The average fiber diameter of the short fibers (H) is preferably 20 to 250 μm, more preferably 100 to 250 μm. When the average fiber diameter of the short fibers (H) is 20 μm or more, the fibers are easily available. When the average fiber diameter of the short fibers (H) is 250 μm or less, the pumpability of the wet material is further improved. By setting the average fiber diameter of the short fibers (H) to 20 μm or more, particularly 100 μm or more, the frictional heat generated when pumping the wet material obtained by adding water to the cementitious material is increased, and the temperature of the wet material discharged from the nozzle tip increases, thereby appropriately shortening the curing time, thereby achieving a continuous higher layering. As the short fibers (H), fibers in the form of bundled fibers in which monofilaments are bundled together with a binder are preferred over monofilament-like fibers, since a larger number of fibers can be mixed in. The number of short fibers (H) per 1 g is preferably 5,000 or more, and more preferably 6,000 or more. When the number of short fibers (H) per 1 g is 5,000 or more, the reinforcing effect and initial crack suppression effect of the short fibers (H) are fully exhibited. The upper limit of the range of the number of short fibers (H) per 1 g is not particularly limited, but is usually 400,000, and preferably 50,000. The number of fibers per 1 g of short fibers (H) is calculated by the following formula using the fineness (dtex) and the mass (g) per 10,000 m of monofilament. Number of fibers (pieces / g) = [1 / (fineness / 10,000(m))] / average fiber length (m / piece) The amount of short fibers (H) used is preferably 0.1 to 1.0 part by mass, more preferably 0.2 to 0.5 parts by mass, per 100 parts by mass of the total of cement (A) and aggregate (G). When the amount of short fibers (H) used is 0.1 part by mass or more per 100 parts by mass of the total of cement (A) and aggregate (G), the reinforcing effect can be further exerted. When the amount of short fibers (H) used is 1.0 part by mass or less per 100 parts by mass of the total of cement (A) and aggregate (G), the short fibers (H) can be further prevented from interfering with pumping.
[0025] <Other ingredients> The wet cement mortar for three-dimensional modeling for construction of the present invention can contain various additives such as antifoaming agents, rust inhibitors, antifreeze agents, shrinkage reducing agents, inorganic minerals such as bentonite and sepiolite, anion exchangers such as hydrotalcite, polymer emulsions, etc. In addition to the inorganic powders premixed with the cement, it is also possible to use inorganic powders with hydration activity such as blast furnace slag, silica fume, and fly ash.
[0026] <Water usage> The dry cementitious material used in the wet cement mortar for construction of the present invention is prepared by adding water and continuously mixing using a continuous mixing system to prepare wet cement mortar for construction of the present invention (hereinafter, sometimes simply referred to as "wet cement mortar") for use in three-dimensional modeling. The amount of water used is preferably 13 to 20 parts by mass, more preferably 15 to 18 parts by mass, per 100 parts by mass of the cementitious material. When the amount of water used is 13 parts by mass or more per 100 parts by mass of the cementitious material, mixing becomes easy. When the amount of water used is 20 parts by mass or less per 100 parts by mass of the cementitious material, an increase in the fluidity of the wet cement mortar is suppressed, and the self-supporting property is further improved.
[0027] <Continuous mixing system> The continuous mixing system used in the wet cement mortar for construction of the present invention will be described below using the continuous mixing system shown in Fig. 1 as an example. Note that the continuous mixing system shown in Fig. 1 does not limit the continuous mixing system used in the wet cement mortar for construction of the present invention. The continuous mixing system used in the wet cement mortar for three-dimensional modeling for construction of the present invention includes a device (a) for continuously supplying dry cementitious materials, a device (b) for continuously supplying water, and a cylindrical mixing device (c) containing a horizontal screw shaft that can continuously mix them to produce wet mortar.
[0028] The device (A) for continuously supplying the dry cementitious material of the continuous mixing system 1 includes a storage hopper 10 and a horizontal screw shaft 70 housed therein, which rotates to guide the dry cementitious material introduced therein to the discharge port 40, and is for feeding the material to the agitation section 50 for continuous mixing. The shape and capacity of the storage hopper 10 are not particularly limited, but a capacity of about 30 to 200 liters is preferred in order to accommodate all repair and reinforcement areas. As for the shape, since the screw shaft 70 is provided at the bottom of the storage hopper, a shape with an inclination is preferred so that the dry cementitious material is naturally fed by the screw shaft 70 without vibration or impact. When the storage hopper 10 is made into a closed system, a cover (not shown) equipped with a pipe outlet and a filter that can only discharge compressed air is attached so that the dry cement mortar transported by air can be stored over the entire material inlet. The cover can be easily removed and fixed to the contact part between the cover and the storage hopper via a rubber packing so that dust does not leak.
[0029] The device (A) for continuously supplying water in the continuous mixing system 1 is a device for stably supplying water via a flowmeter 20 or the like. The water supply position is preferably 0.2 to 1.5 m, more preferably 0.3 to 1.2 m, from the discharge port 40 of the wet cement mortar. When the water supply position is 0.2 to 1.5 m or more from the discharge port of the wet cement mortar, the mixing efficiency is further improved. The amount of water to be supplied may be appropriately set according to the amount of the dry cementitious material that is previously measured. The amount of water to be supplied can be measured by connecting a pipe 30 equipped with a flowmeter 20 to the supply port, and fine adjustment can be performed by providing a needle valve in the pipe 30 and adjusting the opening and closing state of the valve. The water is supplied under a certain water pressure, and the water pressure is preferably 0.2 MPa or more. When the water pressure is 0.2 MPa or more, water can be supplied more stably.
[0030] The cylindrical mixing section 50 in which the screw shaft 70 of the continuous mixing system 1 is housed is capable of continuously producing wet cement mortar by continuously supplying water to the continuously fed dry cementitious material. This is a section for producing wet cement mortar by adding water to the dry cementitious material fed from the storage hopper 10. The cylindrical mixing section 50 is equipped with a mixing blade 60 inside and is connected so as to transmit the rotational motion of the screw shaft 70 of the storage hopper 10. The rotation speed of the mixing blade 60 is preferably 100 to 400 rpm, and more preferably 200 to 300 rpm. When the rotation speed of the mixing blade 60 is 100 rpm or more, the mixing efficiency is improved, and when the rotation speed of the mixing blade 60 is 400 rpm or less, the mortar can be prevented from being heated, causing flow-down and increasing the hardening time.
[0031] [3D modeling method for construction] In the method for three-dimensional modeling for construction of the present invention, the wet cement mortar for three-dimensional modeling for construction of the present invention is pumped by a pump, and the wet mortar for three-dimensional modeling discharged from a nozzle is layered while moving the nozzle to construct a model. The pump is preferably a rotary positive displacement uniaxial eccentric screw pump. The construction-oriented 3D modeling method of the present invention (hereinafter, sometimes simply referred to as "3D modeling method") will be described below using the 3D modeling system 2 shown in Fig. 2 as an example. Note that the 3D modeling method of the present invention is not limited to the 3D modeling system 2 shown in Fig. 2. The 3D modeling method of the present invention can be classified into, for example, a continuous mixing process of dry cementitious material, a pumping process of wet cement mortar obtained by mixing, and a 3D modeling process by controlled nozzle movement.
[0032] The dry cementitious materials of the present invention may be mixed in a continuous mixer 80.
[0033] The pump 90 for pumping the mixed wet cement mortar employed in the present invention is not particularly limited as long as it can pump the wet cement mortar without deteriorating its quality, but a rotary positive displacement uniaxial eccentric screw pump 90 is preferred. The rotary positive displacement uniaxial eccentric screw pump 90 is also called a mono pump or a snake pump, and compared to a squeeze pump, it is capable of pumping a fixed amount of wet cement mortar without pulsation during pumping, and the discharge amount can be adjusted by controlling the motor rotation speed. In addition, the rotary positive displacement uniaxial eccentric screw pump 90 is also preferred in that, due to its structure, it is considered that the temperature of the wet cement mortar being pumped is easily increased, and the hardening reaction of the wet cement mortar progresses in a short time, improving the self-supporting stability and allowing the continuous stacking height to be increased. That is, the rotary volume type uniaxial eccentric screw pump 90 is equipped with a rotor corresponding to a male screw and a stator corresponding to a female screw. When the rotor is inserted into the stator, a sealed space called a cavity (for example, a space between the rotor and the stator) is formed in the gap, and the rotor rotates in the stator, generating a strong suction force, and the cavity moves to the discharge side, thereby continuously transferring the material. During transfer, for example, the rotor performs an eccentric rotational motion in which it rotates while revolving around the central axis of the stator. Then, when the material in the first cavity moves to the previous (discharge side) cavity by suction force, it is considered that it is heated by the frictional resistance with the stator surface. By utilizing such a heating phenomenon, it is possible to realize a three-dimensional modeling with excellent self-supporting stability while ensuring a pot life. For example, the rotary volume type uniaxial eccentric screw pump 90 is exemplified in paragraphs 0063 to 0064 of International Publication No. 2014 / 142239. The pressure-feeding pipe 100 can be a flexible hose with a pressure resistance of 2 to 4 MPa or a partially combined metal pipe, and although it depends on the set discharge amount, the pipe diameter is preferably 20 to 50 mm in inner diameter. The length of the pressure-feeding pipe 100 is not particularly limited, but is preferably 20 m or less in consideration of pumpability.
[0034] A nozzle 110 is provided at the discharge section (the tip of the pressure-transport pipe) that discharges the wet cement mortar of the present invention. The diameter of the discharge port 111 (see FIG. 3) is not particularly limited, but may be appropriately set depending on the diameter of the aggregate used and the width of the stack. For example, if the aggregate diameter is 5 mm or less and the stack width is 50 mm or less, the diameter of the discharge port 111 is preferably 8 to 20 mm. The shape of the discharge port 111 is not particularly limited, but examples include a circle, an ellipse, a rectangle, a cross, a star, and the like, and a brim may be provided around the discharge port in order to provide smoothness to the surface of the discharged wet cement mortar. In these cases, the discharge port 111 is provided perpendicular to the bed 120, but in some cases, the discharge port 111 may be provided horizontally.
[0035] The control of the nozzle movement in the horizontal and vertical directions of the three-dimensional modeling system 2 is preferably performed by fixing the spray nozzle 110 to, for example, a robot arm 130 or a portal plotter and controlling it by a computer. For example, a method is possible in which the three-dimensional data created by a computer is cut at a predetermined thickness to create two-dimensional slice data, and the nozzle 110 is moved in the horizontal direction, such as vertically, horizontally, or diagonally, based on the two-dimensional slice data while discharging wet cement mortar from the spray nozzle 110 onto the bed 120, and the nozzle is moved in the vertical direction repeatedly to sequentially stack the wet material, thereby forming a three-dimensional modeled body 140 (see FIG. 4). Note that when the spray nozzle 110 is fixed to the robot arm 130 or a portal plotter, a pulley 150 is preferably used to prevent the pressure feed pipe 100 from bending and becoming clogged. The moving speed of the nozzle 110 is not particularly limited and can be changed depending on the width of the wet material to be laminated. When the amount of wet material to be discharged is constant, a slower speed increases the width of the wet material to be laminated, and a faster speed decreases the width of the wet material to be laminated. EXAMPLES
[0036] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples.
[0037] <Example 1> A dry cementitious material was prepared by mixing 150 parts by mass of aggregate, 1.0 parts by mass of dispersant with a mass ratio of lignin sulfonate dispersant (R) and melamine sulfonate dispersant (M) of R / M=100 / 200, diutan gum of the type and amount shown in Table 1, 0.25 parts by mass of retarder A, and 20 parts by mass of a mixture of 150 parts by mass of gypsum mixed with 100 parts by mass of calcium aluminosilicate shown in Table 1, and mixing 0.2 parts by mass of short fiber A with respect to the total of 100 parts by mass of cement and aggregate. The supply amount of the dry cementitious material supply part and the water supply part of the continuous mixing device ("Continuous" in Table 1) was adjusted and mixed so that the water was 17 parts by mass with respect to 100 parts by mass of this prepared material. The mortar flow (MF, static and 15 strokes), hardening time and compressive strength of the obtained wet cement mortar were measured, and the thixotropy was calculated. For comparison, the same measurements were also carried out on wet cement mortar mixed using a commercially available batch mixer ("Batch" in Table 1). The results are shown in Table 1.
[0038] (Materials used) <Cement (A)> Cement: Ordinary Portland cement (manufactured by Denka Co., Ltd., Blaine specific surface area 3400 cm 2 / g) <Aggregate (B)> Aggregate: Limestone aggregate (manufactured by Denka Co., Ltd., maximum particle size 1.2 mm, specific gravity 2.71) <Dispersant (C)> Lignin sulfonic acid dispersant (R): Nippon Paper Industries Co., Ltd., product name "Sanex P252" Melamine sulfonic acid dispersant (M): Made by Sika Japan Co., Ltd., product name "Sikament FF86 / 100" <Diutan gum (D)> Diutan gum A: Synthesized by aerobic fermentation of glucose using Alcaligenes microorganisms. Molecular weight: 4.1 million, viscosity of 0.25% by weight aqueous solution: 5600 mPa s Diutan gum B: Synthesized in the same way as diutan gum A, except for the fermentation time. Molecular weight: 2.2 million, viscosity of 0.25% by weight aqueous solution: 2300 mPa s Diutan gum C: Synthesized in the same way as diutan gum A, except for the fermentation time. Molecular weight: 5.3 million, viscosity of 0.25% by weight aqueous solution: 7500 mPa s Diutan gum D: Synthesized in the same way as diutan gum A, except for the fermentation time. Molecular weight 7.8 million, viscosity of 0.25% by weight aqueous solution 9600 mPa s Diutan gum E: Synthesized in the same way as diutan gum A, except for the fermentation time. Molecular weight 1.8 million, viscosity of 0.25% by weight aqueous solution 1800 mPa s <Thickening agents other than diutan gum> Thickener A: Cellulose ether type (manufactured by Shin-Etsu Chemical Co., Ltd., product name "hi90SH-30000" (viscosity of 2% by weight aqueous solution at 20°C is 30,000 mP·s)) <Set retarder (E)> Set retarder A: Citric acid (reagent grade 1) <Amorphous calcium aluminosilicate (F)> Calcium aluminosilicate A: Commercially available special grade reagents SiO2, CaCO3, and Al2O3 were mixed in a specified ratio, heated to about 2000°C in a high-frequency furnace, quenched in water, and pulverized to prepare a material (amorphous, SiO2 content 10.1%, CaO / Al2O3 molar ratio 1.85, Blaine specific surface area 5900 cm). 2 / g) Calcium aluminosilicate B: Prepared in the same manner as calcium silicate A except for changing the mixing ratio of the reagents (amorphous, SiO2 content 14.9%, CaO / Al2O3 molar ratio 1.85, Blaine specific surface area 5800 cm 2 / g) Calcium aluminosilicate C: Prepared in the same manner as calcium silicate A except for changing the mixing ratio of the reagents (amorphous, SiO2 content 24.6%, CaO / Al2O3 molar ratio 1.85, Blaine specific surface area 5800 cm 2 / g) <Gypsum (G)> Gypsum: Natural anhydrous gypsum crushed product (Blaine specific surface area 5200 cm 2 / g) <Short Fiber (H)> Short fiber a: Vinylon fiber (average fiber length 12 mm, average fiber diameter 50 μm, number of fibers per 1 g 55,500)
[0039] (Continuous mixing system) The rotation speed of the stirring blade (60) shown in FIG. 1 was 280 rpm, the distance between the water supply inlet from the water supply pipe (30) and the wet cement mortar discharge outlet (40) was 1 m, and the amount of water supplied was determined by measuring the amount of dry cementitious material discharged per minute in advance, and adjusting the valve while watching the flow meter so that the ratio of water to this was 17 parts by mass. (Commercially available batch mixer) The mixture was mixed using a normal pan mixer with a blade rotating at 45 rpm. The amount of dry cementitious material mixed was 50 kg, and 17 parts by mass of water was added and mixed for 4 minutes.
[0040] (Test Method) All tests were carried out in an environment of 20°C. (1) Blaine specific surface area Measurements were performed in accordance with JIS R 5201-1997. (2) Maximum particle size The aggregate was sieved in accordance with JIS A 1102, and the size of the largest sieve opening that did not pass completely was taken as the maximum particle size. (3) Static and 15-stroke mortar flow (MF) This was in accordance with JIS R 5201. The mortar flow was measured immediately after the flow cone was removed and recorded as the static flow, and then the mortar flow was measured by subjecting it to 15 drops on a flow table and recorded as the 15-hit flow. (4) Thixotropy The flow rate was calculated using the following formula from the difference between the 15 shot flow rate and the static flow rate. Thixotropy (%) = [(15 stroke flow) - (static flow)] / [(static flow) x 100] Thixotropy is a physical property that affects the pumpability and self-supporting properties of layered mortar; the smaller the static flow, the better the self-supporting properties, and the larger the 15-stroke flow, the better the pumpability. (5)Curing time After mixing was completed, 2 kg of the wet material was packed into a plastic bag, and the time when it no longer dented when pressed with a finger was recorded as the hardening time. The finger pressing was done at 2 minute intervals. (6) Compressive strength The mixed material was filled into a 4 x 4 x 16 cm triple formwork conforming to JIS R 5201, and measurements were taken at ages of 3 hours, 12 hours, 1 day, and 7 days. (7) Air content in hardened mortar The observation of the air-void structure was performed according to the linear traverse method of ASTM C 457-98 "Microscopic Determination of Parameters of the Air-Void System in Hardened Concrete." The amount of air after hardening was calculated by dividing the total traverse length of the air bubbles by the total traverse length, and the amount of air in each bubble diameter range was calculated by calculating the total traverse length for each bubble diameter range and dividing it by the total traverse length, and the total amount of air bubbles with diameters of 0.3 mm or less and the total amount of air bubbles with diameters of 0.3 mm or more were calculated.
[0041] [Table 1]
[0042] From Table 1, it can be seen that the wet cement mortar obtained by the continuous mixing system of the present invention using the dry cementitious material within the composition range of the present invention has improved mixing efficiency, reduced air with large bubble diameters, and mixed with a large amount of air with small bubble diameters, and therefore exhibits excellent thixotropy, does not impede pumpability, and can ensure self-support after pumping. Furthermore, it exhibits excellent values for both early strength and long-term strength, and therefore excellent layering speed and construction speed can be obtained. On the other hand, when diutan gum or other thickeners outside the range of the present invention are used, the wet cement mortar obtained by mixing with the batch mixer has poor thixotropy and early strength development, and sufficient layering speed and construction speed cannot be obtained.
[0043] <Example 2> A mixture of 150 parts by mass of aggregate, 0.1 parts by mass of diutan gum A, 0.25 parts by mass of retarder A, and 150 parts by mass of gypsum mixed with 100 parts by mass of calcium aluminosilicate B was mixed with 20 parts by mass per 100 parts by mass of cement, and 0.2 parts by mass of short fiber A was mixed with 100 parts by mass of cement and aggregate to prepare a dry cementitious material. The feed amounts of the dry cementitious material supply unit and the water supply unit of the continuous mixing device were adjusted so that the amount of water was 17 parts by mass per 100 parts by mass of the prepared material. The mortar flow (MF, static and 15 strokes), hardening time and compressive strength of the obtained wet cement mortar were measured, and the thixotropy was calculated. The results are shown in Table 2.
[0044] [Table 2]
[0045] As can be seen from Table 2, the wet cement mortar obtained by combining the lignin sulfonate-based dispersant (R) and the melamine sulfonate-based dispersant (M) within the range of the present invention exhibits excellent thixotropy, does not impair pumpability, and can ensure self-supporting properties after pumping.
[0046] <Example 3> A dry cementitious material was prepared by mixing 150 parts by mass of aggregate, 1.0 part by mass of dispersant with a mass ratio of lignin sulfonate dispersant (R) and melamine sulfonate dispersant (M) of R / M=100 / 200, 0.1 part by mass of diutan gum A, 0.25 part by mass of retarder A, and 20 parts by mass of a mixture with a ratio of calcium aluminosilicate B and gypsum shown in Table 3, and mixing 0.2 parts by mass of short fiber A with respect to the total of 100 parts by mass of cement and aggregate. The supply amount of the dry cementitious material supply part and the water supply part of the continuous mixing device was adjusted so that the water was 17 parts by mass per 100 parts by mass of the prepared material, and the mixture was mixed. The mortar flow (MF, static and 15 strokes), hardening time and compressive strength of the obtained wet cement mortar were measured, and the thixotropy was calculated. The results are shown in Table 3.
[0047] [Table 3]
[0048] It has been found that wet cement mortar obtained by using 50 to 250 parts by mass of gypsum per 100 parts by mass of calcium aluminosilicate has moderate thixotropy and hardening time to ensure self-supporting properties, as well as high compressive strength.
[0049] <Example 4> A mixture consisting of 150 parts by mass of aggregate, 1.0 parts by mass of dispersant with a mass ratio of lignin sulfonic acid dispersant (R) and melamine sulfonic acid dispersant (M) of R / M=100 / 200, 0.1 parts by mass of diutan gum A, 0.25 parts by mass of retarder A, and 150 parts by mass of gypsum per 100 parts by mass of calcium aluminosilicate B was mixed in the amounts shown in Table 4, and 0.2 parts by mass of short fiber A was mixed with 100 parts by mass of cement and aggregate in total to prepare a cementitious material for three-dimensional modeling. The supply amount of the dry cementitious material supply part and the water supply part of the continuous mixing device was adjusted and mixed so that the water was 17 parts by mass per 100 parts by mass of the prepared material. The mortar flow (MF, static and 15 strokes), hardening time and compressive strength of the obtained wet cement mortar were measured, and the thixotropy was calculated. The results are shown in Table 4.
[0050] [Table 4]
[0051] It has been found that wet cement mortar obtained by using a total amount of calcium aluminosilicate and gypsum in an amount of 5 to 30 parts by mass per 100 parts by mass of cement has appropriate thixotropy and hardening time to ensure self-supporting properties.
[0052] <Example 5> For 100 parts by mass of cement, 1.0 parts by mass of aggregate and balloon aggregate shown in Table 5, 1.0 parts by mass of dispersant with a mass ratio of lignin sulfonic acid dispersant (R) and melamine sulfonic acid dispersant (M) of R / M=100 / 200, 0.1 parts by mass of diutan gum A, 0.25 parts by mass of retarder A, and 20 parts by mass of a mixture consisting of 150 parts by mass of gypsum for 100 parts by mass of calcium aluminosilicate B were mixed, and 0.2 parts by mass of short fiber a was mixed for a total of 100 parts by mass of cement and aggregate to prepare a cementitious material for three-dimensional modeling. The supply amounts of the dry cementitious material supply section and the water supply section of the continuous mixing device were adjusted and mixed so that the amount of water was 17 parts by mass for 100 parts by mass of the prepared material. The mortar flow (MF, static and 15 strokes), hardening time and compressive strength of the obtained wet cement mortar were measured, and the thixotropy was calculated. The results are shown in Table 5.
[0053] (Materials used) <Aggregate B> Aggregate: Limestone aggregate (manufactured by Denka Co., Ltd., maximum particle size 1.2 mm, specific gravity 2.71) Balloon aggregate: Tomoe Engineering Co., Ltd., product name "Senolite SA" (a granular product of fly ash balloons generated at thermal power plants, made in China, specific gravity 0.88, maximum particle size 120μm or less)
[0054] [Table 5]
[0055] It is found that the wet cement mortar obtained by using 50 to 300 parts by mass of aggregate per 100 parts by mass of cement has an appropriate thixotropy and hardening time to ensure self-supporting. It is also found that the wet cement mortar obtained by using balloon-type aggregate has increased thixotropy and improved self-supporting property.
[0056] <Example 6> For 100 parts by mass of cement, 150 parts by mass of aggregate, 1.0 part by mass of dispersant with a mass ratio of lignin sulfonic acid dispersant (R) and melamine sulfonic acid dispersant (M) of R / M=100 / 200, 0.1 part by mass of diutan gum A, retarders of the type and amount shown in Table 6, and 20 parts by mass of a mixture consisting of 150 parts by mass of gypsum and 100 parts by mass of calcium aluminosilicate B were mixed, and 0.2 parts by mass of short fiber a was mixed for a total of 100 parts by mass of cement and aggregate to prepare a cementitious material for three-dimensional modeling. The supply amount of the dry cementitious material supply part and the water supply part of the continuous mixing device was adjusted and mixed so that the water was 17 parts by mass for 100 parts by mass of this prepared material. The mortar flow (MF, static and 15 strokes), hardening time and compressive strength of the obtained wet cement mortar were measured, and the thixotropy was calculated. The results are shown in Table 6.
[0057] (Materials used) <Set retarder (E)> Set retarder A: Citric acid (reagent grade 1) Coagulation retarder B: Gluconic acid (reagent grade 1) Coagulation retarder C: Trisodium citrate (reagent grade 1)
[0058] [Table 6]
[0059] It has been found that wet cement mortar obtained by using 0.05 to 0.7 parts by mass of a set retarder containing hydroxycarboxylic acids per 100 parts by mass of cement has thixotropy and hardening time sufficient to ensure self-supporting properties without compromising short-term compressive strength.
[0060] <Example 7> For 100 parts by mass of cement, 150 parts by mass of aggregate, 1.0 part by mass of dispersant with a mass ratio of lignin sulfonic acid dispersant (R) and melamine sulfonic acid dispersant (M) of R / M=100 / 200, 0.1 parts by mass of diutan gum A, 0.25 parts by mass of retarder A, and 20 parts by mass of a mixture consisting of 150 parts by mass of gypsum for 100 parts by mass of calcium aluminosilicate B were mixed, and short fibers of the type and amount shown in Table 7 were mixed for a total of 100 parts by mass of cement and aggregate to prepare a cementitious material for three-dimensional modeling. The supply amount of the dry cementitious material supply part and the water supply part of the continuous mixing device was adjusted and mixed so that the water was 17 parts by mass for 100 parts by mass of this prepared material. The mortar flow (MF, static and 15 strokes), hardening time and compressive strength of the obtained wet cement mortar were measured, and the thixotropy was calculated. The results are shown in Table 7.
[0061] (Materials used) <Short Fiber (H)> Short fiber a: Vinylon fiber (average fiber length 12 mm, average fiber diameter 50 μm, number of fibers per 1 g 55,500) Short fiber B: Nylon fiber (manufactured by Toray Amtex Co., Ltd., product name "Tough Binder" (average fiber length 10 mm, average fiber diameter 28 μm, number of fibers per 1 g 185,200)) Short fiber c: Nylon fiber (manufactured by Toray Amtex Co., Ltd., product name "Tough Binder" (average fiber length 5 mm, average fiber diameter 28 μm, number of fibers per 1 g 370,500)) Short fiber d: Vinylon fiber (manufactured by Kuraray Co., Ltd., product name "RECS100L" (average fiber length 12 mm, average fiber diameter 130 μm, number of fibers per 1 g 8,300))
[0062] (Test Method) Initial crack width: A formwork was set on a concrete slab (30 cm long x 30 cm wide x 6 cm thick), the wet material of the present invention was poured to a thickness of 2 cm, and the surface was finished with a trowel to prepare a test specimen. The test specimen was cured in an environment with a humidity of 60% and a temperature of 5°C, and the crack width after 72 hours was measured. The crack width here refers to the width near the center of the length of any crack that occurred in the test specimen. If no cracks occurred after 72 hours, the width was recorded as 0.0 mm.
[0063] [Table 7]
[0064] It has been found that wet cement mortar obtained by using 0.1 to 1.0 parts by mass of short fibers with an average fiber length of 5 to 15 mm per 100 parts by mass of cement and aggregate combined has the thixotropy and hardening time required to ensure self-supporting properties, while also suppressing initial cracks.
[0065] <Example 8> Using the 3D modeling system 2 shown in Figure 2, 3D modeling experiments were carried out with the mixtures of Experiment No. 1-9, No. 1-50, No. 7-17, and No. 7-18. The environmental temperature was 24°C. At that time, the temperature of the wet cement mortar immediately after mixing in the mixer, the temperature of the wet cement mortar pumped by the rotary positive displacement uniaxial eccentric screw pump 90 and discharged from the discharge port 111 at the tip of the nozzle, the hardening time, and the continuous stacking height were measured. The results are shown in Table 8.
[0066] (3D modeling system) Mixer 80: A continuous mixing mixer according to the present invention Pump 90: Rotary positive displacement uniaxial eccentric screw pump (manufactured by PFT, product name "PFT BOLERO") Pressure pipe 100: 4MPa pressure-resistant flexible hose (PFT, inner diameter 1 inch, pressure pipe length 10m) Nozzle 110: Homemade (see FIG. 3. Note that FIG. 3(a) is a schematic diagram of the spray nozzle seen from the side, and FIG. 3(b) is a schematic diagram of the spray nozzle seen from the outlet side.), nozzle outlet diameter 18 mm (circular) (see reference numeral 111 in FIG. 3(b). Note that the shaded portion indicates the end face of the outlet of the spray nozzle.) Robot arm 130: A modified Yaskawa Electric robot arm (product name "MOTOMAN-MA2010") with a nozzle fixed to the tip of the arm.
[0067] (Modeling conditions) Cementitious material height per layer: 10mm Shape of the three-dimensional object: Truss shape (length 500 mm, width 1000 mm, layer width (thickness) approx. 30 mm) (see Figure 4) Wet material discharge volume: 0.25m 3 / hr, nozzle movement speed: 180mm / sec
[0068] (Test Method) Material temperature: measured with a digital thermometer Curing time: The material discharged from the nozzle tip was sampled and measured in the same manner as in Example 1. Continuous stacking height: Measure the height when stacking the model until it collapses.
[0069] [Table 8]
[0070] The wet cement mortar obtained by the continuous mixing system of the present invention using the dry cementitious material within the composition range of the present invention has excellent thixotropy and can be continuously stacked to a high height. On the other hand, the wet cement mortar obtained by batch mixing, which is outside the range of the present invention, has low thixotropy and cannot withstand the weight of the mortar, making it impossible to continuously stack. [Industrial Applicability]
[0071] By using the wet cement mortar for three-dimensional modeling for construction and the three-dimensional modeling method for construction of the present invention, a constant amount of material can be supplied, and a constant layering speed can be ensured. In addition, since excellent self-supporting properties and strength development (especially initial strength development) can be obtained, a large-sized model can be constructed in a short time. Furthermore, the present invention is less likely to generate dust during molding. Therefore, the present invention can be suitably used for the manufacture of civil engineering and construction components, etc. [Explanation of symbols]
[0072] 1 Continuous mixing system 2. 3D modeling system 10 Storage Hopper 20 Flow meter 30 tubes 40 Outlet 50 Stirring section 60 Stirring blade 70 Screw shaft 80 Continuous Mixer 90 Rotary positive displacement single shaft eccentric screw pump 100 Pressure pipe (flexible hose) 110 Nozzle 111 Discharge port 120 Beds 130 Robot Arm 140 Three-dimensional object 150 Pulley
Claims
1. Cement (A), aggregate (B), dispersant (C) in which the mass ratio of lignin sulfonate-based dispersant (R) to melamine sulfonate-based dispersant (M) is R:M=100:80-400, diutan gum (D) having an average molecular weight in the range of 2 million to 8 million and a viscosity of a 0.25 mass% aqueous solution in the range of 2000 to 10000 mPa s, setting retarder (E), and SiO 2 The method for producing wet cement mortar for three-dimensional modeling for construction uses a continuous mixing system having an apparatus (A) for continuously supplying a dry cementitious material for three-dimensional modeling for construction, the dry cementitious material containing 10 to 25 mass % of amorphous calcium aluminosilicate (F), gypsum (G), and short fibers (H), an apparatus (B) for continuously supplying water, and a cylindrical agitator (C) containing a horizontal screw shaft for continuously mixing the dry cementitious material and wet mortar to produce wet mortar.
2. A method for producing wet cement mortar for construction-use three-dimensional modeling as described in claim 1, wherein the wet cement mortar for construction-use three-dimensional modeling contains 13 to 20 parts by mass of water per 100 parts by mass of the dry cementitious material for construction-use three-dimensional modeling.
3. The method for producing wet cement mortar for three-dimensional modeling for construction according to claim 1, wherein the amount of the dispersant (C) used is 0.2 to 3 parts by mass relative to 100 parts by mass of the cement (A).
4. The method for producing wet cement mortar for three-dimensional modeling for construction according to claim 1, wherein the amount of diutan gum (D) used is 0.03 to 1.0 parts by mass relative to 100 parts by mass of the cement (A).
5. The method for producing a wet cement mortar for three-dimensional modeling for construction according to claim 1, wherein the amount of gypsum (G) used is 50 to 250 parts by mass relative to 100 parts by mass of the amorphous calcium aluminosilicate (F).
6. The method for producing a wet cement mortar for three-dimensional modeling for construction according to claim 1, wherein the total amount of the amorphous calcium aluminosilicate (F) and the gypsum (G) used is 5 to 30 parts by mass relative to 100 parts by mass of the cement (A).
7. The method for producing wet cement mortar for three-dimensional fabrication for construction according to claim 1, wherein the aggregate (B) includes a balloon-type aggregate.
8. The method for producing wet cement mortar for three-dimensional modeling for construction according to claim 1, wherein the setting retarder (E) contains an oxycarboxylic acid.
9. The method for producing wet cement mortar for three-dimensional modeling for construction according to claim 1, wherein the short fibers (H) have an average fiber length of 5 to 15 mm.
10. The method for producing wet cement mortar for three-dimensional modeling for construction according to claim 9, wherein the short fibers (H) have an average fiber diameter of 20 to 250 μm and a number of fibers per gram of 5,000 or more.
11. A method for three-dimensional modeling for construction, comprising the steps of: pumping wet cement mortar for three-dimensional modeling produced by the method for producing wet cement mortar for three-dimensional modeling for construction according to any one of claims 1 to 10; and stacking the wet mortar for three-dimensional modeling for construction discharged from a nozzle while moving the nozzle, thereby constructing a modeled object.
12. The method for constructing solid objects according to claim 11, wherein the pump is a rotary positive displacement uniaxial eccentric screw pump.
Citation Information
Patent Citations
Concrete shear wall structure based on 3D printing and construction method of concrete shear wall structure
CN104153493A
Method for producing precast concrete
CN104308988A
Transmitting and receiving equipment
JP1987010949A
Cement admixture and cement composition
JP1992097932A
Mortar mixing and spraying system and mortar mixing device making use thereof
JP1997317177A
